Kehidupan Penghuni Lanjut Usia di Rumah Susun - Wijaksono, Sigit (Bina Nusantara University, 2012)
Any provision of public facilities and infrastructure should provide accessibility for elderly to create a more supportive situation and environment for them in carrying out their social functions and active roles in community life as naturally, state and nation. Accessibility in this case is the availability of public facilities and infrastructure that can facilitate the mobility of elderly in public places, such as wheelchair ramp, the path for stick users, doors, stairs, elevators for multi-storey buildings, and pedestrian crossing. This accessibility can be both physical and non physical. In this research what to be studied is how the implementation of the existing flats can provide accessibility to the elderly residents. Using descriptive exploratory method the condition of their perceptions of occupied flats will be described. This study is carried out qualitatively using interviews.